Effect of bevacizumab on intracranial meningiomas in patients with neurofibromatosis type 2 – a retrospective case series. (1st November 2016) - Alanin, Mikkel Christian; Klausen, Camilla; Caye-Thomasen, Per; Thomsen, Carsten; Fugleholm, Kaare; Poulsgaard, Lars; Lassen, Ulrik; Mau-Sorensen, Morten; Hofland, Kenneth Francis
Abstract : Purpose : The hallmark of neurofibromatosis type 2 (NF2) is bilateral vestibular schwannomas (VS). Approximately 80% of NF2 patients also have intracranial meningiomas. Vascular endothelial growth factor (VEGF) is expressed in both NF2-related and sporadic occurring meningiomas and anti-VEGF therapy (bevacizumab) may, therefore, be beneficial in NF2-related meningiomas. The purpose of the study was to report the effect of bevacizumab on meningiomas in NF2 patients. Materials and methods : We retrospectively reviewed the effect of bevacizumab on the cross-sectional area (CSA) of 14 intracranial meningiomas in 7 NF2 patients. Bevacizumab 10 mg/kg was administered intravenously every two weeks for six months and 15 mg/kg every three weeks thereafter. Patients were evaluated according to the modified Macdonald criteria with repeated magnetic resonance (MR) scans. Results : The median duration of therapy was 27 months (range 16–34) and 42 MR scans (median 8, range 4–11) were reviewed. The median annual change in meningioma CSA prior to bevacizumab was 2% (range –4%–+76%). During treatment, a decrease in meningioma CSA was observed in 5 of 14 meningiomas (36%) in 5 of 7 patients (71%). The median decrease in CSA was –10% (range –3%––25%). One meningioma (7%) progressed and the remaining (93%) had stable disease. Conclusions : Bevacizumab may slow or reverse the growth of some NF-related meningiomas. However, we have previously reported a fatal case of intracerebral hemorrhage following bevacizumab in NF2 patients, wherefore, this effect needs to be balanced carefully against the risk of side effects.